2018
DOI: 10.2147/ccide.s167152
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on management of traumatic dental injuries among Saudi mothers

Abstract: ObjectiveThis study investigated the knowledge of Saudi mothers regarding the management of traumatic dental injuries (TDIs) in children.Materials and methodsA cross-sectional study using structured questionnaires was employed for mothers chosen by stratified-cluster random sampling technique from primary health care centers in Riyadh, Saudi Arabia, over a period of 12 months (July 2016–June 2017). The questionnaire surveyed mothers’ background and knowledge on management of tooth fracture and avulsion using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(43 citation statements)
references
References 17 publications
2
39
2
Order By: Relevance
“…In the questionnaire questions, it was observed that the parents had correct information about the effect on permanent tooth germs after TDI-p (77.8%), while they had low information about the necessity of going to the dentist (40.7%) and establishing follow-up appointments (25.9%) after TDI-p. This situation does not coincide with the results of mothers who are aware of immediate treatment after TDI-p reported by Al-Sehabiany et al [25]. However, other studies [27,28] concluded that, similar to this study, parents should be made aware of TDI-p. Additionally, Al-Sehabiany et al [25] reported that more than 83% of the mothers wanted to receive further information about TDIs, which is encouraging.…”
Section: False Correct Application Tvcontrasting
confidence: 90%
See 2 more Smart Citations
“…In the questionnaire questions, it was observed that the parents had correct information about the effect on permanent tooth germs after TDI-p (77.8%), while they had low information about the necessity of going to the dentist (40.7%) and establishing follow-up appointments (25.9%) after TDI-p. This situation does not coincide with the results of mothers who are aware of immediate treatment after TDI-p reported by Al-Sehabiany et al [25]. However, other studies [27,28] concluded that, similar to this study, parents should be made aware of TDI-p. Additionally, Al-Sehabiany et al [25] reported that more than 83% of the mothers wanted to receive further information about TDIs, which is encouraging.…”
Section: False Correct Application Tvcontrasting
confidence: 90%
“…It was determined that 37% of the parents were college graduates, 29.6% were university graduates and 44.4% were unemployed. Similarly, in another study, a high level of education was found [25,26]. The fact that most of the parents involved are women and the unemployment rate may mean that most mothers are always available at home and ready to provide first aid if an unfortunate incident of dental trauma occurs, as Al-Sehabiany et al [25] found in their study.…”
Section: False Correct Application Tvmentioning
confidence: 63%
See 1 more Smart Citation
“…High concurrence between the answers to the questions on both occasions was observed. Cronbach’s α was used to test the internal consistency of the questionnaire [ 24 ] which was found to be 0.83.…”
Section: Methodsmentioning
confidence: 99%
“… 5 Unfortunately, there is a deficiency in knowledge, awareness, and immediate management strategies for dental trauma. Al Sehaibiany et al 6 in 2018 suggested a need for effective TDI educational programs to be delivered at primary healthcare levels, which mothers in a survey considered valuable and relevant. At the same time, proper management of TDIs with a satisfying esthetic outcome is essential and a challenging task.…”
Section: Introductionmentioning
confidence: 99%